Police Goes To School Sebagai Bentuk Urgensi Pendidikan Multikulturalisme Polda Kalteng - Rebekka Artauli Lumbantobing (Economy Deposit Journal (E-DJ), 2022)
Differences cause conflict if not accompanied by tolerance in it. This study aims to identify the role of the Central Kalimantan Regional Police in Police Goes To School as a Form of Urgency in the Central Kalimantan Regional Police's Multiculturalism Education. The preparation of this work uses a qualitative method with a descriptive type approach. Data collection techniques in the preparation of this work using interviews, observation and documentation. The analysis used by the author in compiling this work uses a descriptive type. The results of the preparation of this work are Police Goes to School when visiting schools with 1) Police goes to school Traffic Education from an Early Age, 2). Socialization of the Importance of Using SNI Helmets, 3). Socialization of road signs and markings, and 4). Children in an Orderly Health Protocol and Orderly Covid Prevention Program from an early age. Meanwhile, other materials which include the urgency of multiculturalism education when Police Goes to School are 1). As an alternative means of conflict resolution, 2). So that students are not uprooted from cultural roots, and 3). Towards a multicultural Indonesian society